Extracorporeal Membrane Oxygenation for Coronavirus Disease 2019: Crisis Standards of Care. Issue 3 (March 2021) - Agerstrand, Cara; Dubois, Richard; Takeda, Koji; Uriel, Nir; Lemaitre, Philippe; Fried, Justin; Masoumi, Amirali; Cheung, Eva W.; Kaku, Yuji; Witer, Lucas; Liou, Peter; Gerall, Claire; et al.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has placed extraordinary strain on global healthcare systems. Use of extracorporeal membrane oxygenation (ECMO) for patients with severe respiratory or cardiac failure attributed to COVID-19 has been debated due to uncertain survival benefit and the resources required to safely deliver ECMO support. We retrospectively investigated adult patients supported with ECMO for COVID-19 at our institution during the first 80 days following New York City's declaration of a state of emergency. The primary objective was to evaluate survival outcomes in patients supported with ECMO for COVID-19 and describe the programmatic adaptations made in response to pandemic-related crisis conditions. Twenty-two patients with COVID-19 were placed on ECMO during the study period. Median age was 52 years and 18 (81.8%) were male. Twenty-one patients (95.4%) had severe ARDS and seven (31.8%) had cardiac failure. Fifteen patients (68.1%) were managed with venovenous ECMO while 7 (31.8%) required arterial support. Twelve patients (54.5%) were transported on ECMO from external institutions. Twelve patients were discharged alive from the hospital (54.5%). Extracorporeal membrane oxygenation was used successfully in patients with respiratory and cardiac failure due to COVID-19. The continued use of ECMO, including ECMO transport, during crisis conditions was possible even at the height of the COVID-19 pandemic.